The Influence of Accessibility, Quality of Facilities and Information Technology on Public Satisfaction in the Education Sector - Gus Endrawan; Dasman Lanin; Erianjoni Erianjoni; Aldri Frinaldi (Khazanah Sosial, 2024)
The importance of this research is to assess the level of community satisfaction with the education sector in Kampar Kiri Hulu District, Kampar Regency, Riau Province. This research looks at the influence of accessibility, quality of facilities and information technology on public satisfaction in the education sector. The method chosen was quantitative by collecting data through questionnaires distributed to people living in Kampar Kiri Hulu District. The population in this study is the heads of households who have children enrolled in schools and reside in the territorial area of the Kampar Kiri Hulu District. The total population is 3,386 households, and the sample is 357 households. Primary data for this research will be obtained by the researcher through questionnaires from the community that has enrolled their children, while secondary data will be obtained from websites, online journals, literature studies, and related research references. Data analysis techniques include descriptive analysis, multiple linear regression, classical assumption tests, and hypothesis testing. The data will be processed using SPSS 0.26. The results of this research are the magnitude of the influence of accessibility on community satisfaction in the education sector 30.8%, the magnitude of the influence of facility quality on community satisfaction in the education sector 32.5%, the magnitude of the influence of information technology on community satisfaction in the education sector 30.6% and the magnitude the influence of accessibility, quality of facilities and information technology together is 47.1%. Judging from the magnitude of this influence, the closer the figure is to 100%, the better the public's satisfaction in education sector. This study is academically interesting because it provides public knowledge about the level of community satisfaction in the education sector, especially in Kampar Kiri Hulu District, Kampar Regency, Riau Province.